Determination of frequency distribution of HLA-DR1-7 antigens in various forms of oral lichen planus with PCR test - Ferial Dormiani Tabatabaei; Gholam Reza Jahanshahi; Parichehr Ghalyani (Isfahan University of Medical Sciences, 2011)
Introduction: Lichen planus is a chronic mucocutaneous disease with unknown etiology and pathogenesis. It is thought that immunological (humoral and cellular) disorders and genetic factors, such as HLA, are involved in its pathogenesis. This study evaluated and compared frequency distribution of HLA-DR1-7 antigens in various forms of oral lichen planus.Materials and methods: This retrospective case-control study was carried out on 66 lichen planus patients from May 2009 to August 2010. The subjects were evaluated in 6 groups of 11. After clinical and pathological confirmation of oral lichen planus, whole blood samples were obtained for evaluation of HLA-DR1-7 presence with PCR. Data was analyzed by chi-square, t-test, and Cochran and McNemar tests (α = 0.05).Results: There was a significant difference in HLA-DR2 antigen frequency, with the highest and lowest frequencies in the bullous and plaque-like forms, respectively. HLA-DR3 antigen frequency was the highest in the papular and the lowest in the reticular and bullous forms and it appeared to have a significantly higher frequency in the plaque-like form compared to the reticular and bullous forms. HLA-DR4 antigen had the highest and lowest frequencies in the erosive and papular forms, with significantly higher frequencies in the reticular and erythematous forms compared to the papular form. HLA-DR7 antigen had the highest and lowest frequencies in the plaque and bullous forms, with significantly lower frequencies in the reticular, erythematous, and popular forms compared to the plaque-like form.Conclusion: Under the limitations of the present study it was concluded that the frequency of some HLA-DR antigens were significantly different in various OLP forms. The possible effect of these antigens on the incidence of some forms of OLP necessitates further studies on the subject. Key words: HLA, Oral lichen planus, PCR.